THE ENVIRONMENT OF THE SUN DURING THE EXPLOSION OF CORONAL MASS EJECTIONS (CMES) ON 2ND MAY 2016 - Roslan, Umar; Z. S., Hamidi; N. M., Shariff (2018)
Coronal Mass Ejections (CMEs) have been studied has become the most important phenomena of solar activity because it is the most energetic phenomena on the Sun. Concerning the importance of the impact of solar radio burst, we study the selected event of CMEs to observe the environment of the atmosphere of the Sun. It was found that the geomagnetic field was at active to severe storm conditions due to continued activity from the active region. The sunspot number is 76 and radio flux exceeds 92 sfu. There are eight sunspots and with a density of 2.9 proton/ cm 3 . During that event, solar wind also reached up to 540.6 kmsec -1 . It is recommended to collect data for 5 years and above in order to observe the trend of the graph between SRBT II and the speed of CMEs